Perceived Organizational Support and Employee Well-Being: A Quantitative Study of Employees at CV. X, a Dairy Processing Company in Indonesia - Habela Gustin Robeta; Sutarto Wijono (Universitas PGRI Yogyakarta, 2025)
Digital transformation has increased job demands, making employee well-being a key organizational concern. This is particularly relevant for companies in the dairy industry, such as CV. X. POS is considered a crucial factor influencing well-being, yet previous research shows mixed results. This study examines the relationship between POS and employee well-being at CV. X. Using a quantitative approach with saturated sampling, the study involved 121 employees. The instruments used were the Perceived Organizational Support Survey (16 items, α = 0.913) and the Employee Well-Being Scale (18 items, α = 0.905). Data were analyzed using Pearson correlation with SPSS 24. The results showed a positive and significant relationship between POS and employee well-being (r = 0.889; p < 0.05). These findings highlight the importance of organisational support policies in improving employee well-being and suggest practical interventions for HR management. Keywords: perceived organizational support, employee well-being, employee